Analysis of the broadcasting and perceived utility through the implementation of a virtual training platform during the pandemic - Sánchez-Santos, Raquel; Morales-Conde, Salvador; Ramos Rodriguez, Jose Luis; Alvarez Peña, Estibaliz; Aranda Narváez, Jose Manuel; Alvarez Gallego, Mario; Badía, Josep María; Balibrea del Castillo, Jose Maria; Garcia-Botella, Alejandra; Guirao Garriga, Xavier; Espin Basany, Eloy; Martin-Antona, Esteban; et al. (Cirugia española (English ed.), 2023)
The SARS-CoV-2 pandemic has affected training opportunities for healthcare professionals partly because face to face courses were cancelled. This study analyzes the results of participation and satisfaction of the AEC Virtual Classroom sessions during the first year. The AEC Virtual Classroom includes a combined format of weekly Webinar broadcast live that can be viewed on a delayed basis in a virtual platform. In this study, the results in its first year are evaluated considering the number of live participants, the delayed views and the global reach; as well as the results of the satisfaction survey in each of the sessions (0–10). From 16/04/2020 to 15/04/2021, 50 sessions of the Virtual Classroom AEC were held. The average scope of the sessions was 509 ± 288 views with a range between 196 and 149. At the times of highest incidence of cases during the pandemic, a decrease in live participants was observed 275 ± 135 vs. 391 ± 233 (P = 0.032). The mean score on the format was 8.46 ± 0.31/10. The best-scored sessions were those of the subject related to coloproctology with a statistically significant difference in the mean score 8.79 ± 0.42 vs. 8.39 ± 0.27 (P = 0.035). 90% of users considered the sessions useful. 97.2% of respondents believe that the sessions should be maintained after the pandemic. The AEC Virtual Classroom has had very good results in the first year, proving to be a useful surgical teaching tool that will foreseeably survive once the pandemic is over. La pandemia de COVID-19 ha afectado a las oportunidades de formación de los profesionales sanitarios, en parte porque se anularon muchos cursos presenciales. En este estudio se analizan los resultados de participación y satisfacción de las sesiones del Aula Virtual AEC durante su primer año. El Aula Virtual AEC incluye un formato combinado de seminarios semanales emitidos en directo que pueden ser visionados en diferido. En este estudio se evalúan los resultados en sus primeros 12 meses, considerando el número de participantes en directo, el número de visualizaciones en diferido y el alcance global, así como los resultados de la encuesta de satisfacción realizada en cada una de las sesiones (1-10). Desde el 16 de abril de 2020 hasta el 15 de abril de 2021 se realizaron 50 sesiones del Aula Virtual AEC. El alcance medio de las sesiones ha sido de 509 ± 288 visualizaciones con un rango entre 196 y 1490. En los picos de la pandemia se observó un descenso de los participantes en directo: 275 ± 135 vs. 391 ± 233 (p = 0,032) La puntuación media sobre el formato fue 8,46 ± 0,31/10. Las sesiones mejor puntuadas fueron las de temática relacionada con coloproctología con una diferencia estadísticamente significativa en la puntuación media 8,79 ± 0,42 vs. 8,39 ± 0,27 (p = 0,035). Un 90,76% de usuarios consideraron las sesiones útiles. Un 97,2% consideraban que deben mantenerse tras la pandemia. El Aula Virtual AEC ha tenido muy buenos resultados en los primeros 12 meses de desarrollo, resultando ser una herramienta útil de docencia quirúrgica que previsiblemente sobrevivirá a la época de pandemia.